Sikap Normalisasi Obesitas oleh Netizen dalam Gerakan Body Positivity di Media Sosial - Jannatania, Jasmin; Ramadhanti, Galuh Aulia (Jurnal Media dan Komunikasi Indonesia, 2025)
The body positivity movement which is rife on social media is currently increasingly worrying because of the emergence of the attitude of normalizing those who have overweight bodies to obesity. The purpose of this study was to find out the answers given by the influencers and netizen of the body positivity (bopo) movement when given a statement regarding the glorification of obesity. Virtual ethnographic methods are used in this study because of its reality in the form of social media. The findings of this research there are three results that are the attitude of the influencers and netizen of the bopo movement: (1) being positive, (2) the attitude of 'My Body My Rules', and (3) debate using research data. It was obtained that the influencers and netizen of this bopo movement continued to use these three things when debating about the body weighted more that had looked unhealthy anymore.